Peran Cerita Rakyat dalam Membentuk Karakter Anak - Maulani, Syafina; Faridah, Faridah; Putri, Putri; Ardiansyah, Dedek (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Folklore as a cultural expression of a group contains moral and educational values that play a role in the social structure of society. Through folklore, children can gain new understandings that they may not have experienced before. However, folklore is now starting to be forgotten, so that the younger generation who are expected to be the nation's successors do not understand the important role of folklore in character formation. This research aims to shape children's character, strengthen cultural identity, and build a moral foundation through the integration of folklore in formal and informal education. With a literature study approach, this study analyzes relevant literature to understand how folklore can be used in the formation of children's characters. The results of the study emphasized the importance of preserving folklore as an effective means of shaping the character of the younger generation in the era of globalization, by strengthening their understanding of the values of kindness, traditions, and how to face life's challenges